Hardware implementation of the Central Solar Battery Charging Station (CSBCS) - Ahmed, Omaer; Sunny, Syed Md. Musa; Ferdous, Wasefa (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.